Nasr Hamid Abu Zayd as a Modern Muslim Thinker - Zainol, Nur Zainatul Nadra (International journal of islamic thought, 2014)
Nasr Hamid Abu Zayd is a thinker who has produced works in the fields of theology, philosophy, law, politics and humanities. Abu Zayd’s thought, partly on the Quran and its hermeneutics has stirred controversy in Egypt and the Muslim world. This research focuses on the controversy surrounding Nasr Hamid Abu Zayd which led to the declaration of his apostasy by the Supreme Court of Egypt in 1995, as well as his controversial thoughts on the Quran, its method of exegesis and certain fiqh (Islamic jurisprudence) issues such as the hijab (veil) and polygamy. This paper serves as a literature review which employs the content analysis as a methodology to elaborate on Abu Zayd’s controversial thoughts based on his books, as well as through the views of Muslim and Western scholars on those thoughts.